Internalisasi Praktik Beragama: Kontribusi Madrasah Pada Pembentukan Karakter Pemuda Indonesia - Diana Rohali; Afifah Afifah (Fakta: Jurnal Pendidikan Agama Islam, 2021)
This research aim to describe:  1. How the process of  internalizing religious values through exemplary and habituation method in Ad-dzikir Pragaan elementary school. 2. What are supporting and inhibiting factors of internalizing religious values through exemplary and habituation method in Ad-dzikir Pragaan elementary school.  This research used qualitative approach, informan of this research are principal, master of classes, and students of Ad-Dzikir. Data collection technique used are observation, interview and documentation. Data analysis  used are data reduction, data presentation and conclusion.  The result showed that the process of  internalizing religious values through exemplary method in Ad-dzikir Pragaan elementary school are ilahiyah values, insaniyah values, akhlaq values.  The teacher behavior as role models are: discipline, on time both in school or class, appreciated students tasks, became imam when dhuhur  prayer, assertive, gave advice and motivation.  The process of  internalizing religious values through   habituation method in Ad-dzikir Pragaan elementary school are time, condition and program habituation.